THE EFFECT OF GIVING GREEN BETEL LEAF EXTRACT ON THE GROWTH OF Bacteroides IN VAGINAL SECRET CULTURE - Nuraini, Deswinda Fadhilah; Yanti, Ni Luh Gede Puspita; Parwati, Putu Ayu; Prihatiningsih, Diah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Green betel leaves contain compounds that can treat vaginal discharge, especially those caused by bacteria. To determine the effect of green betel leaf extract on the growth of Bacteroides in vaginal secretion cultures, this study used a quantitative experimental method, where vaginal secretion samples were taken from the subjects and then tested quantitatively. There were two data collection techniques used in this study: using a questionnaire and testing vaginal secretion samples with green betel leaf extract. The test for using was diffusion (paper disc) for the antibacterial test. The media used was MHA. The positive control used was a blank disc, the extract concentration series used were 20%, 25% and 30%. The diameter of the inhibition zone was observed and then analyzed. The results of the t-test analysis showed that the significance value was 0.00 <0.05, so H0 was rejected Ha was accepted or it could be concluded that there was a difference in the effect of giving green betel leaf extract on the growth of Bacteroides in vaginal secretion culture. Antibacterial activity test of green betel leaves (Piper betle L) against Bacteroides bacteria that cause Bacterial Vaginosis, namely resistant at a concentration of 20%, intermediate at a concentration of 25% and sensitive at a concentration of 30%. Green betel leaf extract (Piper betle L) has inhibitory power against Bacteroides bacteria that cause Bacterial Vaginosis. Can increase the concentration series of methanol extract of green betel leaves, find the minimum bactericidal concentration (MBC) and the maximum inhibitory concentration (MIC) of green betel leaf extract against Bacteroides bacteria that cause Bacterial Vaginosis